Teaching Writing Descriptive Text by Using Mind Mapping to SLL Bimbel English Course Learner - Yuce Matamtaza (P-SEMART JOURNAL, 2021)
This research purposed to describe how the teacher teaching writing uing mind mapping in the class, to describe how the progress of the student’s writing ability when describing things, and to describe how the students’ responses to describing things in teaching writing. This study used descriptive qualitative method. The data were taken from the tenth grades students of SLL Bimbel English Course Learner, class X TPM 4 with 10 number of students. The data collecting technique used observation field note, student’s performance on describing, and questionnaire. From the result of observation, the researcher could say that teaching writing using descriptive for describing things could make them confidence to write English without being worried about the vocabulary and structures mistakes. Based on the student’s performance on describing, the researcher could say that the students enjoyed their dialogue for describing things although they were ashamed to practice describing in front of the class. Teaching writing using describing with their friend also made the students confidence and bravery to write English. Based on the students’ responses, it could be said that the teaching writing using descriptive for describing things in the class was enthusiastic.